Spirituality in ministerial formation : the dynamic of prayer in learning - Mayes, Andrew D. (Religion, education, and culture., 2009)
This is a ground-breaking study into a crucial area of theological education. It traces the origin and evolution of the formation model of training and identifies what difference this paradigm makes to present practice.